Rheological behavior of graphite induced anisotropic magnetorheological elastomer - Shabdin, Muhammad Kashfi (2020)
The rheological properties of magnetorheological elastomer (MRE) with graphite (Gr) was evaluated in the present research. Two types of MRE samples namely anisotropic MRE and GrMRE were fabricated with Gr as a filler during MRE fabrication. The effect of Gr as filler on the rheological properties of MRE was experimentally investigated and compared with those of conventional MREs. Rheological properties under different magnetic fields at zero-field modulus and on-state of 4 A were evaluated under oscillatory rheometer test. Moreover, the effect of curing conditions of GrMRE towards the MR effect was thoroughly examined. It was observed that with the addition of Gr, the rheological properties such as the storage modulus are improved, particularly at low strain amplitudes which showed that the initial storage modulus increase at 48% for both off- and on-state conditions when compared between GrMRE and reference sample without Gr while less dissipation of energy detected in both sample as the loss modulus does not change so much. In addition, the values of MR effect were found to increase in conventional MRE at 32.8% while GrMRE showed 28.3% of MR effect, in which, this kind of finding could be practically used in the fabrication process of potential sensing devices.